(untitled) (Homoeopathy for All, 2025)
Chronic diseases continue to exert a heavy burden on global health, with a significant proportion rooted in hereditary predispositions. This article explores the potential of ho moeopathy as a therapeutic modality for addressing inherited tendencies to chronic ailments. Drawing upon classical homoeopathic literature, clinical methodologies, and personal motivations, this study aims to eval uate the efficacy of individualized homoeopathic treatment in modu lating hereditary predispositions to chronic diseases.